Jewish Mad Men : Advertising and the Design of the American Jewish Experience - Steinberg, Kerri P., 1959- (Book collections on Project MUSE., 2015)
"It is easy to dismiss advertising as simply the background chatter of modern life, often annoying, sometimes hilarious, and ultimately meaningless. But Kerri P. Steinberg argues that a careful study of the history of advertising can reveal a wealth of insight into a culture. In Jewish Mad Men, Steinberg looks specifically at how advertising helped shape the evolution of American Jewish life and culture over the past one hundred years. Drawing on case studies of famous advertising campaigns--from Levy's Rye Bread ("You don't have to be Jewish to love Levy's") to Hebrew National hot dogs ("We answer to a higher authority")--Steinberg examines advertisements from the late nineteenth-century in New York, the center of advertising in the United States, to trace changes in Jewish life there and across the entire country. She looks at ads aimed at the immigrant population, at suburbanites in midcentury, and at hipster and post-denominational Jews today. In addition to discussing campaigns for everything from Manischewitz wine to matzoh, Jewish Mad Men also portrays the legendary Jewish figures in advertising--like Albert Lasker and Bill Bernbach--and lesser known "Mad Men" like Joseph Jacobs, whose pioneering agency created the brilliantly successful Maxwell House Coffee Haggadah. Throughout, Steinberg uses the lens of advertising to illuminate the Jewish trajectory from outsider to insider, and the related arc of immigration, acculturation, upward mobility, and suburbanization. Anchored in the illustrations, photographs, jingles, and taglines of advertising, Jewish Mad Men features a dozen color advertisements and many black-and-white images. Lively and insightful, this book offers a unique look at both advertising and Jewish life in the United States"--